2012
DOI: 10.1007/s10971-012-2688-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of novel titanium dioxide doped with silver

Abstract: Pure and silver doped nanoparticles of titanium dioxide (TiO 2) was prepared using novel, modified sol-gel method. The samples were characterized by transmission electron microscopy, X-ray diffraction, N 2 adsorption measurement, atomic absorption spectroscopy (AAS), UVvis spectroscopy (UV-vis). The antibacterial activity of the prepared samples was indicated by minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (MBC) values according to the reference methods of Clinical and Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 26 publications
2
42
1
5
Order By: Relevance
“…Owing to the highly oxidative nature of these species, also the cell walls and membranes of microorganisms can be destroyed, thus inducing a truly antimicrobial effect (Fig. 70) [423,429,[444][445][446][447].…”
Section: Contaminant Degradationmentioning
confidence: 99%
“…Owing to the highly oxidative nature of these species, also the cell walls and membranes of microorganisms can be destroyed, thus inducing a truly antimicrobial effect (Fig. 70) [423,429,[444][445][446][447].…”
Section: Contaminant Degradationmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has a strong killing effect on all kinds of bacteria under UV irradiation, while metal (Cu, Co, Ni, Cr, Mn, Mo, Nb, V, Fe, Ru, Au, Ag, Pt)-doped-TiO 2 and nonmetal (N, S, C, B, P, I, F)-doped-TiO 2 exhibits high antibacterial activity, even under visible light [9][10][11][12][13][14]. Due to their chemical stability, non-toxicity, and capacity to be repeatedly used without losing activity, these inorganic compounds have demonstrated usefulness as disinfection or sterilization reagents for water and air purification, self-clean solid surfaces, and food protection.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the phytochemical present in fruit peels 20 are responsible for synthesis of Cu-doped nanoparticles that itself acts as stabilizers in synthesis 15 thus special capping agent/ stabilizer is not required. As plant extract is used instead of organic chemicals, this method omits the use of conventional chemicals like isopropyl alcohol 21 , ethanol 22 , polyvinyl alcohol 23 , etc. On the other hand, plant extract is prepared in water with waste peels.…”
Section: Introductionmentioning
confidence: 99%